STUDI TENTANGMAHASISWA BERPRESTASI DI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS RIAU - Maimunah "; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research describes about student’s achievement in social and political science university of Riau. This subject is student’s who was named the standings at graduation in 2013 and 2014, by formulating the problem of characteristics of oustanding students, environment and activities. This research used qualitative research methods and data collection methods, namely purposive sampling. This research uses analitif-descriptive method. The datas were obtained from internet, journals, and books. Then, they were collected, summarized and analyzed based on the social research method.This research uses the theory of David McClelland about Motivation Theory and Needs. And then, theory of Emile Durkheim about Education Morality. And at least, theory of Max Weber about Social Activities.Keywords: Student’s Achievement, Motivation Theory, Social Activities